2019
DOI: 10.1080/09297049.2019.1614156
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in absence epilepsy during long-term follow-up

Abstract: Absence epilepsy (AE) has been associated with lower than average cognitive functioning, which are clinically relevant in some and may predispose to problems later in life. This study aimed to assess cognitive development during long-term follow-up in children with AE. Thirty-one children with AE, who had undergone two neuropsychological assessments between 2010 and 2017 were analyzed retrospectively. Cognitive measurements were 1.7 ± 0.95 years apart. The difference in neurocognitive test scores was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In this study, the high IISL was correlated with cognitive impairment. These results agree with Fonseca et al [29] who found that suppression of interictal epileptiform discharges (IEDs) is associated with improved cognitive functions in children with epilepsy. These results were also consistent with the outcomes of Ung et al [30] who reported that frequent IEDs in more than 10% of the record can impair cognitive performance in children.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the high IISL was correlated with cognitive impairment. These results agree with Fonseca et al [29] who found that suppression of interictal epileptiform discharges (IEDs) is associated with improved cognitive functions in children with epilepsy. These results were also consistent with the outcomes of Ung et al [30] who reported that frequent IEDs in more than 10% of the record can impair cognitive performance in children.…”
Section: Discussionsupporting
confidence: 92%
“…Attention involves several different components and partially overlap with executive functions; previous studies showed that children with epilepsy exhibit a wide range of attention difficulties (D'Alessandro et al, 1990;Gascoigne et al, 2017;Semrud-Clikeman & Wical, 1999) and a high percentage of inattentivetype ADHD (Dunn & Kronenberger, 2005;Gascoigne et al, 2017). However, a cross-sectional design (e.g., Cnaan et al, 2017;D'Alessandro et al, 1990;Deonna et al, 2000;Fonseca Wald et al, 2019;Masur et al, 2013;Shinnar et al, 2017), short follow-up periods and a lack of proper age bias correction (Cnaan et al, 2017;Glauser et al, 2010;Masur et al, 2013;Shinnar et al, 2017) are significant limitations of these studies, making further confirmation necessary. In this regard, our paper based on well-defined eligibility criteria, comparable protocols, and an extended follow-up -confirmed this observation, showing a high percentage of attention deficits without significant differences in frequency between the three groups of examined patients in our cohort.…”
Section: Discussion Of Our Results On Attentionmentioning
confidence: 96%
“…The anomalous interictal epileptiform activity may momentarily disrupt cortical processing as well [32,42]. A follow-up retrospective survey [43] assessed the main cognitive fields (i.e., intelligence, attention visualperceptual function, language, memory, and learning) in 31 children with CAE or JAE, based on Baron's distinction of neurocognitive domains in children [44]. In this study, educational achievements were also included, collected with reports and academic evaluations filled by school-specialists.…”
Section: Cognition In Absence Epilepsymentioning
confidence: 99%